Semi-fluorinated alkane eye drops reduce signs and symptoms of evaporative dry eye disease after cataract surgery - Son, Hyeck Soo; Yildirim, Timur Mert; Khoramnia, Ramin; Poompokawat, Piyanut; Knorz, Michael C.; Auffarth, Gerd U. (Journal of refractive surgery, 2020)
Purpose: To clinically evaluate the efficacy and tolerability of semi-fluorinated alkane eye drops (EvoTears; URSAPHARM GmbH) as ocular surface treatment after cataract surgery in patients with evaporative dry eye disease. Methods: This prospective, monocentric, open-label clinical trial included 40 patients undergoing cataract surgery and showing symptoms of evaporative dry eye disease as measured by the Symptom Assessment in Dry Eye (Visual Analogue Scale [VAS]) questionnaire, Ocular Surface Disease Index (OSDI), and tear break-up time (TBUT) of less than 10 seconds. EvoTears was prescribed four times a day for 5 weeks and administered 15 minutes after the standard postoperative topical anti-inflammatory regimen. The primary endpoint was the change in TBUT. Secondary endpoints included assessment of the subjective symptoms (VAS), corrected distance visual acuity (CDVA), slit-lamp examination, intraocular pressure, and Schirmer's test, which were evaluated at 1 day, 1 week, and 5 weeks postoperatively. At 5 weeks postoperatively, the tolerability and efficacy of EvoTears were evaluated by physicians and patients. Results: At 5 weeks postoperatively, the median TBUT increased from 6.8 (preoperative) to 14 seconds (P < .001) and the average total corneal staining score decreased from 3.53 (preoperative) to 2.36 (P < .001). The mean CDVA improved from 0.41 (preoperative) to 0.14 logMAR (P < .001) and there was a statistically significant decrease in all scores from the VAS questionnaire at 5 weeks postoperatively. There was no statistically significant change in Schirmer's test (P = .150). Conclusions: EvoTears improved tear film, ocular surface, and subjective impressions of patients with dry eye disease 5 weeks after cataract surgery. Patients' and physicians' assessment indicated good efficacy and high tolerability of EvoTears, suggesting its suitability in postoperative management of the ocular surface in patients with dry eye disease.
Gesehen am 01.10.2020